(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تمت في هذا البحث دراسة تأثير الوسط المتأين وأشعة بيتا على عملية تشكل نواة جسيمة جديدة في الهواء، ومن ثم التأكد من ارتباط شحنة هذه النواة( الجسيمة المتشكلة) ونصف قطرها الحرج بثوابت الوسط المتأين. وقد تبين أن تأثير أشعة بيتا على عملية تشكل النواة يؤدي إلى شيئين متعاكسين: الأول: تحت تأثير جسيمات بيتا يحدث تغير في شحنة النواة وهذا يقود بدوره إلى زيادة نصف القطر الحرج للنواة المتشكلة، مع زيادة عدد جسيمات بيتا( زيادة شدة الإشعاع). الثاني: إن تسخين جسيمات بيتا للغاز يقود إلى زيادة نسبة التأين للوسط ونقصان نصف القطر الحرج لنواة المتشكلة. Influence of ionization environment and - radiations on processes of nucleation rate at atmospheric pressure in air is surveyed. Dependence of a charge and critical radius of a particle nucleus on parameters of ionized environment is determined. It is shown that the action of - particles on nucleation goes in two opposite-direction tendencies. On the one hand, under the actions of - particles, there is a change of a charge of nucleus that causes an increment in critical radius of a nucleus with increasing intensity of radiation. On the other hand, having warmed up gas of - particles leads to an increment of the ionization degree of the environment and to the diminution of critical radius of the nucleus.